Genetic diversity and prevalence of piroplasm species in equids from Turkey - Ozubek, Sezayi; Aktas, Munir (Elsevier Sci Ltd, 2018)
Equine piroplasmosis (EP) is a protozoon disease caused by Babesia caballi and Theileria equi transmitted by ticks from the Ixodidae family. This study investigated the genetic heterogeneity and diversity of piroplasm genotypes using the Reverse Line Blotting (RLB) technique for piroplasm species in equids in Turkey. A total of 233 blood samples from 142 horses and 91 donkeys were collected in Sanliurfa, Tunceli, and Igdir. The RLB assay was performed for simultaneous detection of piroplasm species. The prevalence of piroplasm infection was 33.5% (95% CI; 27.4-39.9). T. equi was the most common species (%20.2; 95% CI 15.2-25.9), whereas B. caballi infection was not detected. Nine samples hybridized to the Theileria/Babesia and Theileria catch-all probes but did not hybridize to any species-specific probe tested, suggesting the presence of unrecognized Theileria variants or genotypes. Nine samples that gave Theileria spp. signal and two samples that gave T. equi specific signal were sent for sequence analysis and the A and D genotypes of T. equi were found. In addition, T. annulata, B. ovis, and B. canis species were detected in the samples and verified by sequence analysis in Turkey. More research is needed to understand the clinical impact of atypical piroplasm infections in equids.
Keywords: Piroplasms; Theileria equi; Reverse line blot; 18S rRNA gene; Equids; Turkey